-3e+97=100

Simple and best practice solution for -3e+97=100 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3e+97=100 equation:


Simplifying
-3e + 97 = 100

Reorder the terms:
97 + -3e = 100

Solving
97 + -3e = 100

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Add '-97' to each side of the equation.
97 + -97 + -3e = 100 + -97

Combine like terms: 97 + -97 = 0
0 + -3e = 100 + -97
-3e = 100 + -97

Combine like terms: 100 + -97 = 3
-3e = 3

Divide each side by '-3'.
e = -1

Simplifying
e = -1

See similar equations:

| 0=x^2-19x+48 | | 5x+6/4=-6 | | (1/8)^-1/3 | | 4^7/2 | | -3(a-2)=-4(2-a) | | (-64)^-1/3 | | -4y+5=-10x^2+6y | | 5-8b+6-2= | | -x=2x-15 | | 5f+3B=5.70 | | (-8)^3/2 | | -34=-6x+3x+2 | | -2(x-3)=-3(2-4/3x) | | 16+4x(7+8)-3=65 | | 7(-5-x)=8(-13) | | 9k-(5k-14)= | | 1=3-3z | | (8X-2)+(3-5X)=(X-3) | | x-4/6=×/2 | | 6x-3=-2x+21 | | 5x+3+3x=-77 | | 5/8^ | | 10p-3=2(12+8p)-7 | | 18x-x^2-3x^3-6=0 | | 9/4*5/8 | | g(x)=f(-4x) | | 25.2/-.4 | | 4*5/8-1/4 | | 10p-3=2(12+p)-7 | | p^2+4*p+2=0 | | (k-1)x*x+4k-1=(3+4k)x | | x=-7/2 |

Equations solver categories